Społeczny marketing w procesach adaptacji idei zmian - Iwankiewicz-Rak, Barbara; Rak, Lech (Social Marketing in the Processes of Idea Adoption and Changes, 2006)
The article shows features and rules of social marketing whose aim is to introduce social changes. The marketing tools are presented and rules of cooperation between non-governmental organizations and media in the area of transferring these ideas to society.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 37-47